PERBEDAAN PERILAKU ETIS PEJABAT PENATAUSAHAAN KEUANGAN DAN BENDAHARA SKPD BERDASARKAN FAKTOR INDIVIDUAL DALAM ETIKA PENYUSUNAN LAPORAN KEUANGAN SATUAN KERJA PERANGKAT DAERAH (SKPD) DI KABUPATEN SAROLANGUN - Eva Setiarini Damanik (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The purpose of this study is to obtain empirical evidence related to significant differences in ethical behavior between PPK and Treasurer SKPD based on individual factors in the preparation of financial statements SKPD as measured by disclosure, cost and benefit, responsibility, misstate, and timeliness of the preparation of financial statements SKPD. This study will examine whether there are significant differences in ethical behavior between PPK and SKPD Treasurer based on individual factors in the preparation of SKPD financial statements that can be measured by disclosure, cost and benefit, responsibility, misstatement, and timeliness of SKPD financial report preparation. In this study, the disclosure, cost and benefit, responsibility, misstate, and timeliness variable of SKPD financial statements as variables will be measured and compared between two sample groups (PPK and SKPD Treasurer) which have different individual factors (locus of control, long time, gender, equity sensitivity, educational background and self efficacy. The results of data testing related to the analysis of individual factors of PPK and SKPD Treasurer at the Local Government of Sarolangun Regency in the ethics of preparation of financial statements SKPD There is no difference between PPK and SKPD Treasurer with internal locus of control to PPK and Treasurer SKPD with external locus of control in ethics of preparation SKPD's financial statements to the Sarolangun Regency Government are expressed by the variable cost and benefit and timeliness. Keywords: Role of PPK and Treasurer SKPD, Financial Statement Preparation Ethics, Financial Statement SKPD Sarolangun